1990
DOI: 10.1115/1.2899582
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hardness on Residual Stresses in Orthogonal Machining of AISI 4340 Steel

Abstract: Residual stress remaining in machined parts can be detrimental. Previous experimental evidence shows that hardness has a significant effect on its formation. Yet, no satisfactory explanation is available for the causes of such a phenomenon. This work seeks to understand the mechanism of residual stress formation and explain the effect of hardness on it. The analysis is based on the existence of several measurable factors that influence the stress field in the work-material during the cutting process. The sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…Matsumoto et al [5] showed that the residual stresses obtained from the machining of AISI 4340 steel are tensile for low hardness levels but become compressive as hardness increases. For the same material, Wu and Matsumoto [6] showed that the residual stress pattern is linked to the orientation of the primary shear deformation zone in metal cutting. In most cases, a tensile residual stress state is found on the machined surface.…”
Section: Introductionmentioning
confidence: 98%
“…Matsumoto et al [5] showed that the residual stresses obtained from the machining of AISI 4340 steel are tensile for low hardness levels but become compressive as hardness increases. For the same material, Wu and Matsumoto [6] showed that the residual stress pattern is linked to the orientation of the primary shear deformation zone in metal cutting. In most cases, a tensile residual stress state is found on the machined surface.…”
Section: Introductionmentioning
confidence: 98%
“…The extant literature reports various concerns that restrict its exploitation, the foremost of which is the unexpected failure of the machined component while in use [1][2][3][4]. Such failure is believed to be due to the formation of the white layer both on and underneath the finished machined surface [2,[5][6][7][8] caused by the tensile residual stresses on the machined surface [9][10][11][12][13][14]. This imposes serious risks regarding the potential fatigue life of components [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Barash [1] showed that residual stress strongly depends on various parameters including work hardness, phase transformation, tool wear, and cutting conditions. Wu and Matsumoto [2] showed that work hardness is the most influencing factor responsible for the residual stress. In a study on the mirror cutting of hardened steel, Oishi [3] suggested that the roughness of a machined surface can be improved by suppressing the formation of the built-up edge chip if the hardness of the built-up edge chip is less than twice the hardness of the work.…”
Section: Introductionmentioning
confidence: 99%